The relationship between executive functions and fluid intelligence in schizophrenia - Roca, María; Manes, Facundo; Cetkovich, Marcelo; Bruno, Diana; Ibáñez, Agustín; Torralva, Teresa; Duncan, John (Frontiers in Behavioral Neuroscience, 2014)
We believe that such finding has strong clinical and methodological implications that we hope we have further explained with the changes made in the manuscript.